0.5(6c-4)=4+c

Simple and best practice solution for 0.5(6c-4)=4+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(6c-4)=4+c equation:


Simplifying
0.5(6c + -4) = 4 + c

Reorder the terms:
0.5(-4 + 6c) = 4 + c
(-4 * 0.5 + 6c * 0.5) = 4 + c
(-2 + 3c) = 4 + c

Solving
-2 + 3c = 4 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
-2 + 3c + -1c = 4 + c + -1c

Combine like terms: 3c + -1c = 2c
-2 + 2c = 4 + c + -1c

Combine like terms: c + -1c = 0
-2 + 2c = 4 + 0
-2 + 2c = 4

Add '2' to each side of the equation.
-2 + 2 + 2c = 4 + 2

Combine like terms: -2 + 2 = 0
0 + 2c = 4 + 2
2c = 4 + 2

Combine like terms: 4 + 2 = 6
2c = 6

Divide each side by '2'.
c = 3

Simplifying
c = 3

See similar equations:

| 12m-15m^3=0 | | 13x+8=18x-7 | | 3(x+4)+23=-4x | | 6g^3-23gh+15h^2=0 | | 16y^2+8yz-3z^2=0 | | x-14=-24 | | 2x-1.5=6 | | 2x^2+6y^2+3=4x^2-8y+4 | | 6(x-2)=-3x+42 | | 2+4x=x+11 | | 5x-3(x-1)-7=2(x-2) | | 4t+9+(2t+7)= | | -6=6+k | | -3(x-4)+7=-2x | | (4x^2-3x)(6x+5)=0 | | 3x-25=11x-5+2x | | 5(x-3)=2x+21 | | 5y+2x=25 | | 26+4y-4=16y-13-5y | | 3x-0.25y=-2 | | x+0.20(3)=0.60(x+3) | | 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 |

Equations solver categories